2013
DOI: 10.1209/0295-5075/101/46001
|View full text |Cite
|
Sign up to set email alerts
|

Structure-dependent vibrational properties of metallic nanoclusters

Abstract: The thermally vibrational properties of icosahedral (ICH) and face-center-cubic (FCC) copper nanoclusters have been compared by carrying out molecular dynamics simulations with a local-environment-dependent tight-binding potential. Although both ICH and FCC copper nanoclusters exhibit a low-and high-energy enhancement of vibrational density of states (VDOS) in comparison with the bulk copper, the vibrational properties of nanoclusters show a strong structure-dependent feature. The different structure is reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 22 publications
4
18
0
Order By: Relevance
“…Therefore, the phonon specific heat can be theoretically obtained if g(ω) is known. The previous studies have shown that the surface VDOS is scaled as g(ω)∼ω 1.5 and the core VDOS as g(ω)∼ω 2 at low frequencies [9][10][11]24]. This implies the spatial dimension n=2.5 for surfaces and n=3 for the core.…”
Section: Theoretical Analysis and Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Therefore, the phonon specific heat can be theoretically obtained if g(ω) is known. The previous studies have shown that the surface VDOS is scaled as g(ω)∼ω 1.5 and the core VDOS as g(ω)∼ω 2 at low frequencies [9][10][11]24]. This implies the spatial dimension n=2.5 for surfaces and n=3 for the core.…”
Section: Theoretical Analysis and Discussionmentioning
confidence: 93%
“…This is different from the pure 2D system. In this sense, the spatial dimension of surfaces should be between 2D and 3D [9][10][11].…”
Section: Theoretical Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[21] For example, exploiting the symmetry breaking in supported metal nanoparticles (NPs), Carles' group developed a technique to directly measure the vibrational density of states (VDOS). [22,23] Such a breakthrough [24] lead to the understanding of intricate experimental results using well established theoretical results, [21,[25][26][27][28][29] which link the VDOS as a NP vibrational fingerprint that correlates to the morphology of the system. [18,21] Contrasting these results, organic macro-molecules' spectroscopy relies only on Raman and IR spectroscopy to experimentally study them.…”
Section: Introductionmentioning
confidence: 99%